Consumer Attitudes & Purchase Intentions: Study of Consumer Buying Behavior towards Organic Food in Pakistan - Abbasi, Muhammad Nauman; Abbasi, Sahibzadi Zartashia (2017)
Purpose of this study is to examine the underlying motives which build an attitude towards purchase of organic food (vegetables) in Pakistan. Grounded from literature, ecological motives, health orientation and convenience (location & availability) were selected as factors motivating consumers to buy organic food.General survey guided by well-structured questionnaire through convenience sampling has been administered across a valuable sample of 300 organic food buyers & consumers.Based on valid response, 292 responses were finally accepted for analysis.Data has been analyzed in AMOS 18. Existing literature lacks well established theoretical foundation to explain purchase behavior of organic food users. Therefore, guided by the Theory of Reasoned Action (TRA) and Theory of Planned Behavior (TPB), it appears that ecological motives and health orientation and consciousness significantly influence the attitudes of the buyers for the purchase of organic food, while, convenience in terms of location & availability insignificantly affect purchasers’ behavior.Interestingly, attitudes towards buying of organic food mediate the relationship between ecological motives, health orientation, convenience and intention to purchase organic food.Results also indicate that attitude had a significant as well as positive relationship with intention to purchase organic food. Finally, trust level of buyers’ towards seller claim of selling pure organic food moderates relationship between attitude and intentions to prefer organic food yet intensity of relationship remained weaker.This paper recommends that organic food sellers in Pakistan may use appeals that contain theme like, ‘environmental friendliness’ and ‘health consciousness’ to arouse consumer interest towards purchase of organic food.